A new fragmentation- and physical layer impairments-aware algorithm to core and spectrum assignment in spatial division multiplexing elastic optical networks - Lacerda Jr., J. C.; Morais, A. G.; Cartaxo, A. V. T.; Soares, A. C. B. (Annales des Télécommunications, 2025)
Spatial division multiplexing elastic optical networks (SDM-EONs) based on multicore fibers (MCFs) are a technology that can handle the Internet’s growing traffic demand. However, SDM-EONs present challenges in their implementation, such as the physical layer impairments (PLI) and the spectrum fragmentation. This paper proposes the fragmentation-aware and PLI-aware algorithm (FXAA) to solve the core and spectrum assignment problem in MCF-based SDM-EONs. The FXAA implements a low-cost PLI-aware mechanism to select lightpaths with low inter- and intra-core impairment incidence, ensuring the quality of transmission (QoT) of the network lightpaths. In addition, FXAA clusters the lightpaths with the same number of frequency slots to reduce spectrum fragmentation. The numerical results show that compared with the other nine algorithms proposed in the literature, FXAA achieves a gain of circuit blocking probability of at least 33.36%, a gain of bandwidth blocking probability of at least 17.99%, and an increase in spectral utilization of at least 1.08%.